Interactive video in higher education: Edpuzzle as a tool for teaching Economic History - Castro-Valdivia, Mariano; Vázquez-Fariñas, María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The irruption of ICT in university education has allowed the development of mobile learning. In this context, the authors of this paper analyse how the use of interactive video tools is a useful instrument in Higher Education and in the assessment of competences. For this purpose, they use the video editing tool Edpuzzle in some of the practice groups of the Economic History course of the Degree in Business Administration and Management at the University of Jaén. The teaching innovation experience has been carried out during the first four-month period of the academic year 2021-2022.